Respuesta :
Answer:
x = 0.75
Step-by-step explanation:
Simplifying
(7x + -5) + -1(3x + -2) = 0
Reorder the terms:
(-5 + 7x) + -1(3x + -2) = 0
Remove parenthesis around (-5 + 7x)
-5 + 7x + -1(3x + -2) = 0
Reorder the terms:
-5 + 7x + -1(-2 + 3x) = 0
-5 + 7x + (-2 * -1 + 3x * -1) = 0
-5 + 7x + (2 + -3x) = 0
Reorder the terms:
-5 + 2 + 7x + -3x = 0
Combine like terms: -5 + 2 = -3
-3 + 7x + -3x = 0
Combine like terms: 7x + -3x = 4x
-3 + 4x = 0
Solving
-3 + 4x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + 4x = 0 + 3
Combine like terms: -3 + 3 = 0
0 + 4x = 0 + 3
4x = 0 + 3
Combine like terms: 0 + 3 = 3
4x = 3
Divide each side by '4'.
x = 0.75
Simplifying
x = 0.75
Answer:
When solving equations like this, you have to use a method called PEMDAS.
This stands for:
P- Parentesis
E- Exponents
M- Multiply
D- Divide
A- Addition
S- Subtraction
(7x + 5) - (3x +2)
Let's work it out...
Step one) Distribute the equation
Distributing the equation helps simplify it and make solving much easier.
(7x−5) − 1(3x−2)
(7x−5) − 3x + 2
Step two) Eliminate the Parenthesis
Now that the equation is simplified, you can take out the Parenthesis.
(7x − 5) − 3x + 2
7x − 5 − 3x + 2
Step three: Add the numbers
Add the two whole numbers together (-5 + 2)
7x − 5 − 3x + 2
7x − 3 − 3x
Step four: Combine like terms
Combine like terms or the numbers with variables (7x - 3x)
7x − 3 − 3x
4x − 3
Solution
4x - 3
Hope this helped! :)